ANALISA KEKUATAN PUNTIR, LENTUR PUTAR DAN KEKERASAN BAJA ST 60 UNTUK POROS PROPELLER SETELAH DIQUENCHING - Sarjito, Sarjito; Jokosisworo, Jokosisworo (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2009)
In the propeller rotation to obtain the ship thrust, the shaft occurred the vary of pressures as the effect of the force combination. The pressures continuously happened and it cause fatique on the material. Therefore the heat treatment occurred to produce high destructive resistance and to gain the good strength. In this research thr heat treatment ic processed by Quenching, slight cooling and used oil as the cooling media.This research objected to know the mechanical and physical type of material such as ultimate strength, yield strength, twisting, rotating bending, hardness and the composition of ST 60 stell after being Quenching will be compared to the ST 60 stell without Quenching, those material used as the propulsion material. The material was ST 60 stell, contained carbon 0,35-0,4% C. The test occurred for both type, they are physical type (composition) and mechanical type ( hardness, ultimate strength, twisting and rotating bending). The spesiment being heat at the temperature of 850º C during 20 menit and being oiled Quenching, then the test of bending, twisting, rotating bending, composition and hardness are occurred.In accordance to the research. The ultimate strength ST 60 after being Quenched is 860, 27 N/mm², yield strenght is 695,95 N/mm², the Brinell hardness is 263,209, the material compositions are 0,5% C, 0,75% Mn, 0,34% Si, 0,0098% P, 0,0009% S, rotating bending strenght is 337,08 Mpa with the 1.298.600 sicluses and twisting strength is 21,07 Mpa.